System for assistance on bath of bedridden elderly people - Bezerra, Karolina Celi Tavares (2015)
From Ambient Assisted Living (AAL) perspective it is important to have information regarding the type of care needed by bedridden elderly people (BEP) living in their homes, in order to support independence, autonomy and maximize their quality of life. Some basic tasks as eating, taking a bath and the hygiene cares may be difficult to execute, regarding that almost always the main caregiver is the other element of the couple (husband or wife). Following this trend, the development of mechatronic devices is of upmost importance in creating solutions to facilitate these tasks. This paper presents the conceptual design of a mechatronic system especially devoted to the assistance during the bath of BEP. Issues as reducing the number of caregivers to only one to assist the bath and reducing the system's handling complexity (because most of the time it will be used by an aged person) are considered. Visits to rehabilitation centers and hospitals, and respective working meetings, are considered in the development of the proposed mechationic system.